High-transmittance high-wear-resistance glass radiant refrigeration heat-insulation coating and preparation method thereof

CN122917580APending Publication Date: 2026-10-16SHAANXI LIBI HIGH-TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611344582.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-01
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0002]随着现代建筑采光设计普及,大面积玻璃幕墙、落地玻璃窗、采光顶得到广泛应用,但普通钠钙硅浮法玻璃对太阳光中780~2500nm近红外热辐射几乎无阻隔作用,夏季太阳辐射热量大量涌入室内,直接导致室内升温快、空调持续高负荷运行,建筑制冷能耗大幅攀升,不符合国家建筑节能降碳政策要求

Benefits of technology

[0030] The coating of this invention has excellent interfacial adhesion. The silanol groups in the coating undergo covalent condensation with the silanol groups on the glass surface to form a continuous Si-O-Si anchoring structure. The adhesion rating is 0 in the cross-cut adhesion test. After 1000 cycles of high and low temperature (-30℃ to 70℃) and 5000 hours of accelerated UV aging, there is no peeling, flaking, or cracking.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application is suitable for the technical field of building energy-saving glass, and provides a high-transmittance high-wear-resistance glass radiation refrigeration heat-insulation coating and a preparation method thereof.The coating contains, by mass fraction, 35-50 parts of tetraethyl orthosilicate, 40-60 parts of anhydrous ethanol, 8-15 parts of deionized water, 0.3-1.2 parts of a weak acid catalyst, 1.2-3.5 parts of amino silane coupling agent modified defective g-C3N4 nanosheet, 0.15-0.6 parts of a metal chelating agent, 0.2-0.8 parts of a shear thinning rheological additive and 0.1-0.5 parts of an ultraviolet stabilizing additive.The application builds an inorganic-organic hybrid network and uses amino silane modified defective g-C3N4 as a functional filler, so that the coating has excellent visible light transmittance, near-infrared heat resistance and atmospheric window infrared emissivity, and has ultrahigh hardness and long-term weather resistance, and has a wide application prospect in the field of building energy saving.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building energy-saving glass technology, specifically a high-transmittance, high-wear-resistant glass radiation cooling and heat insulation coating and its preparation method. Background Technology

[0002] With the popularization of modern building lighting design, large-area glass curtain walls, floor-to-ceiling windows, and skylights are widely used. However, ordinary soda-lime float glass has almost no blocking effect on the 780-2500nm near-infrared thermal radiation in sunlight. In summer, a large amount of solar radiation heat enters the room, directly causing the indoor temperature to rise rapidly, the air conditioner to run at a high load continuously, and the building's cooling energy consumption to rise sharply, which does not meet the requirements of the national building energy conservation and carbon reduction policy.

[0003] To address the aforementioned issues, the market currently employs several solutions: Replacing with Low-E insulated glass involves high costs for overall procurement, dismantling, and installation, long construction periods, significant safety risks during dismantling and installation on high-rise curtain walls, and is only suitable for new buildings; large-scale renovation of existing buildings is extremely uneconomical. Applying architectural insulation film presents challenges such as air accumulation and blistering between the film and glass, edge delamination, cracking and aging under long-term UV exposure, high-altitude installation on high-rise facades is difficult, and requires complete replacement every 3-5 years, resulting in high overall maintenance costs. While external sunshades and louvers can block direct sunlight, they obstruct indoor views, damage the building's appearance, and cannot block long-wave infrared radiation heat transfer, offering limited insulation. In the cutting-edge field of passive radiative cooling, photonic crystals and multilayer optical thin-film cooling materials offer high spectral control precision, but their preparation relies on precision vacuum equipment, resulting in complex processes, high costs, and limited widespread application.

[0004] Existing polymer-based composite cooling coatings are low-cost and easy to apply, but they generally suffer from problems such as insufficient spectral matching, high near-infrared heat absorption, and limited infrared emissivity. To improve emissivity, coating hardness and weather resistance are often sacrificed, leading to chalking and light transmittance degradation under long-term UV exposure. It is difficult to simultaneously achieve both abrasion resistance and outdoor service performance. Therefore, there is an urgent need to provide a high-transmittance, high-abrasion-resistant glass radiation cooling and heat insulation coating and its preparation method to overcome the shortcomings in current practical applications. Summary of the Invention

[0005] The purpose of this invention is to provide a high-transmittance, high-wear-resistant glass radiation cooling and heat insulation coating and its preparation method, aiming to solve the problems in the background art mentioned above.

[0006] This invention is achieved as follows: a high-transmittance, high-wear-resistant glass radiation cooling and heat insulation coating, comprising, by weight, the following raw materials:

[0007] 35-50 parts of tetraethyl orthosilicate;

[0008] 40-60 parts of anhydrous ethanol;

[0009] 8-15 parts deionized water;

[0010] 0.3–1.2 parts of weak acid catalyst;

[0011] 1.2–3.5 parts of aminosilane coupling agent were used to modify defective g-C3N4 nanosheets;

[0012] Metal chelating agent 0.15–0.6 parts;

[0013] 0.2–0.8 parts of shear-thinning rheology modifier;

[0014] 0.1 to 0.5 parts of UV stabilizer.

[0015] As a further aspect of the present invention: the aminosilane coupling agent is 3-aminopropyltriethoxysilane;

[0016] The weak acid catalyst is glacial acetic acid;

[0017] The metal chelating agent is aluminum acetylacetonate.

[0018] As a further aspect of the present invention, the defective g-C3N4 nanosheets are prepared by thermal etching of flake-shaped C3N4 powder at 520°C under a nitrogen atmosphere.

[0019] As a further aspect of the present invention: the coating has a visible light transmittance of ≥85% in the 380-780nm band, a near-infrared blocking rate of ≥90% in the 780-2500nm band, and an atmospheric window infrared emissivity of ≥0.95 in the 8-13μm band.

[0020] As a further aspect of the present invention: the dry film of the coating has a pencil hardness ≥5H, and is scratch-free after being repeatedly rubbed with steel wool 25,000 times.

[0021] The present invention also provides a method for preparing the high-transmittance, high-wear-resistant glass radiation cooling and heat insulation coating as described above, comprising the following steps:

[0022] Step 1: The flake-like C3N4 powder is thermally etched to create defects, resulting in defect-modified carbon nitride nanosheets; the defect-modified carbon nitride nanosheets are mixed with anhydrous ethanol and an aminosilane coupling agent, and ultrasonically exfoliated and surface modified to obtain an aminosilane coupling agent modified defect g-C3N4 nanosheet dispersion.

[0023] Step 2: Mix tetraethyl orthosilicate and anhydrous ethanol evenly, and slowly add a mixture of deionized water and a weak acid catalyst to carry out a hydrolysis and polycondensation reaction to generate silica sol; add a metal chelating agent to the silica sol and stir evenly to obtain a stable silica sol base liquid;

[0024] Step 3: Add the aminosilane coupling agent modified defect g-C3N4 nanosheet dispersion to the stabilized silica sol substrate solution. After uniform dispersion, add the shear-thinning rheology modifier and the UV stabilizer, and mix evenly to obtain the final product.

[0025] As a further aspect of the present invention: in step 1, the temperature of the thermal etching process is 520°C, the time is 2 hours, and the atmosphere is nitrogen.

[0026] The ultrasonic ablation process took 4 hours.

[0027] As a further aspect of the present invention: in step 2, the hydrolysis-condensation reaction is carried out at room temperature and the stirring time is 2.5 hours.

[0028] As a further aspect of the present invention: in step 3, the aminosilane coupling agent is added to modify the defective g-C3N4 nanosheets using a high-speed dispersion method, with a dispersion speed of 1200 r / min and a dispersion time of 40 minutes.

[0029] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0030] The coating of this invention has excellent interfacial adhesion. The silanol groups in the coating undergo covalent condensation with the silanol groups on the glass surface to form a continuous Si-O-Si anchoring structure. The adhesion rating is 0 in the cross-cut adhesion test. After 1000 cycles of high and low temperature (-30℃ to 70℃) and 5000 hours of accelerated UV aging, there is no peeling, flaking, or cracking.

[0031] With excellent optical performance, the coating has a visible light transmittance of 88.7% and a haze of only 1.1%, so indoor lighting is not affected. It has a near-infrared blocking rate of 94.2% across the entire 780-2500nm wavelength band and an infrared emissivity of 0.96 in the 8-13μm atmospheric window. It also has outstanding passive radiation cooling effect. Compared with the same working conditions in a sealed glass room in summer, the indoor temperature can be reduced by up to 8.6℃, and the air conditioning energy consumption is reduced by more than 37%.

[0032] It has outstanding mechanical, abrasion-resistant and weather-resistant properties. The dry film pencil hardness is 6H. It can withstand 25,000 cycles of abrasion-resistant steel wool without scratches and has a light transmittance attenuation of less than 1.2%. It has an inorganic silicon network synergistic with UV stabilizers, and its outdoor natural stability service life can reach 15 years. It is resistant to rain and salt spray for 1200 hours without corrosion or loss of gloss.

[0033] With strong construction adaptability, the coating exhibits typical shear thinning characteristics. When placed vertically for 72 hours on high-rise curtain walls and sloping skylights, there is no sagging or shrinkage cavities. It cures at room temperature without the need for heating or baking. A single person can complete up to 210m² of work per day. 2 .

[0034] The renovation cost is low, with the raw material cost of paint per square meter being only 45 to 70 yuan. There is no need to dismantle the original glass. Compared with replacing Low-E glass and high-end heat insulation film, the overall renovation cost is reduced by more than 60%, making it suitable for energy-saving renovation of large-area existing buildings.

[0035] The filler exhibits excellent dispersibility; the aminosilane-grafted modified carbon nitride nanosheets are completely monolayer dispersed without agglomeration or precipitation. The coating shows no stratification, whitening, or precipitation after 90 days of static storage, demonstrating excellent storage stability. Detailed Implementation

[0036] The technical solution of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0037] The following are representative embodiments of the coating composition and preparation method of the present invention.

[0038] The high-transmittance, high-wear-resistant glass radiation cooling and heat insulation coating provided by this invention comprises, by weight, the following raw materials: 35-50 parts of tetraethyl orthosilicate, 40-60 parts of anhydrous ethanol, 8-15 parts of deionized water, 0.3-1.2 parts of a weak acid catalyst, 1.2-3.5 parts of aminosilane coupling agent to modify defective g-C3N4 nanosheets, 0.15-0.6 parts of a metal chelating agent, 0.2-0.8 parts of a shear-thinning rheology modifier, and 0.1-0.5 parts of a UV stabilizer. Preferably, the aminosilane coupling agent is 3-aminopropyltriethoxysilane, the weak acid catalyst is preferably glacial acetic acid, and the metal chelating agent is preferably aluminum acetylacetonate. The defective g-C3N4 nanosheets are prepared by thermal etching of flake-like C3N4 powder at 520°C under a nitrogen atmosphere.

[0039] Explanation of the function of each raw material:

[0040] Tetraethyl orthosilicate: an inorganic precursor of silica sol, which hydrolyzes and condenses to form a continuous Si-O-Si inorganic hard network, covalently bonded to the glass substrate, providing a high-hardness, wear-resistant, and weather-resistant substrate;

[0041] Anhydrous ethanol: Dispersing solvent, regulates the hydrolysis rate of sol, improves the spreadability of coatings, and reduces the porosity of coating films;

[0042] Deionized water: provides the water source for the hydrolysis reaction and precisely controls the degree of polycondensation reaction;

[0043] Weak acid catalyst (glacial acetic acid): gently catalyzes the stepwise and controllable hydrolysis of tetraethyl orthosilicate, avoiding the formation of large-particle silica sol from localized rapid condensation, and ensuring that the film is uniform and dense;

[0044] Aminosilane coupling agent modified defect g-C3N4 nanosheets: core spectral modulation functional filler; defect engineering optimizes band structure, near-infrared plasma effect blocks solar thermal radiation, high infrared emission through 8-13μm atmospheric window achieves radiative cooling; aminosilane grafted to the surface of the sheet, steric hindrance inhibits stacking and agglomeration, and reduces coating haze.

[0045] Metal chelating agent (aluminum acetylacetonate): chelates silicon hydrolysis intermediates, delays excessively rapid local condensation, and prevents uneven film thickness and internal micropore defects;

[0046] Shear-thinning rheology modifier: Under shearing action during roller / spray coating, the viscosity of the paint decreases rapidly, resulting in smooth spreading; after static curing, the viscosity recovers rapidly, and there is no sagging when applied to vertical surfaces.

[0047] UV stabilizer: Works synergistically with the silicon network to shield UV light, slowing down the photo-oxidative degradation of carbon nitride filler and extending its outdoor service life.

[0048] The present invention also provides a method for preparing the above-mentioned coating, comprising the following steps:

[0049] Step 1: Modification of defective g-C3N4 nanosheets using aminosilane coupling agents

[0050] 1) Place the flake-shaped C3N4 powder in a tube furnace and heat-etch defects at 520℃ for 2 hours in a nitrogen atmosphere to obtain defect-modified carbon nitride nanosheets.

[0051] 2) Mix the coarse material with anhydrous ethanol, add 3-aminopropyltriethoxysilane coupling agent, ultrasonically exfoliate for 4 hours, centrifuge to remove unexfoliated and stacked particles, and obtain a monolayer C3N4 dispersion.

[0052] Step 2: Preparation of silica sol substrate solution

[0053] 1) Mix tetraethyl orthosilicate and anhydrous ethanol and stir for 10 min to obtain a mixed alcohol solution;

[0054] 2) Premix deionized water and glacial acetic acid weak acid catalyst evenly, and slowly add it dropwise to alcohol solution. Stir at room temperature at a constant speed for 2.5 h to complete stepwise hydrolysis and condensation, and generate uniform nano silica active sol with a particle size of 10-25 nm.

[0055] 3) Add acetylacetone metal chelating agent to the silica sol and stir for 30 min to regulate gel kinetics and obtain a stable silica sol substrate solution.

[0056] Step 3: Preparation of composite thermal insulation coating

[0057] 1) Add pre-modified C3N4 nanosheets to the silica sol substrate solution and stir at 1200 r / min for 40 min using a high-speed disperser to ensure that the filler is monodisperse and free from agglomeration;

[0058] 2) Add shear-thinning rheology modifier and hindered amine UV stabilizer in sequence, stir at low speed for 20 minutes to mix evenly, filter with a 200-mesh filter to remove trace impurities, and obtain the finished glass heat insulation coating.

[0059] The present invention will be further described below through specific embodiments.

[0060] Example 1:

[0061] Pre-modified defective C3N4 nanosheets: bulk carbon nitride thermal etching at 520℃ with nitrogen, ultrasonic exfoliation with ethanol, graft modification with 3-aminopropyltriethoxysilane at 60℃, ready for use.

[0062] Preparation of silica sol: 42 parts of tetraethyl orthosilicate and 52 parts of anhydrous ethanol were mixed; 11 parts of deionized water and 0.7 parts of glacial acetic acid were mixed and slowly added dropwise, and the mixture was stirred for 2.5 hours for hydrolysis; 0.35 parts of aluminum acetylacetone chelating agent were added and stirred for 30 minutes.

[0063] Paint preparation: Add 2.4 parts of modified carbon nitride and disperse at 1200 r / min for 40 min; add 0.5 parts of polyether rheology modifier and 0.3 parts of hindered amine UV modifier in sequence, stir at low speed for 20 min, and filter through 200 mesh to obtain the finished paint.

[0064] Two coats of glass were applied by roller coating, and the film was cured at room temperature for 24 hours to form a dry film with a thickness of 8μm.

[0065] Performance test results: visible light transmittance 88.7%, haze 1.1%, near-infrared blocking rate 94.2%, infrared emissivity 0.96; pencil hardness 6H; no scratches after 25,000 abrasion and washing cycles; 1.0% transmittance decay after 5,000 hours of UV aging; no shedding after 1,000 high and low temperature cycles; temperature reduction of 8.6℃ per square meter, and energy saving of 37.5% for air conditioning.

[0066] Example 2:

[0067] Raw material weight parts: 35 parts tetraethyl orthosilicate, 40 parts anhydrous ethanol, 8 parts deionized water, 0.3 parts glacial acetic acid, 1.2 parts modified carbon nitride, 0.15 parts aluminum acetylacetonate, 0.2 parts rheology modifier, and 0.1 parts UV auxiliaries; preparation and construction steps are the same as in Example 1.

[0068] Performance: Visible light transmittance 91.2%, near-infrared blocking rate 90.1%, pencil hardness 5H, estimated outdoor lifespan 12 years.

[0069] Example 3:

[0070] Raw material weight parts: 50 parts tetraethyl orthosilicate, 60 parts anhydrous ethanol, 15 parts deionized water, 1.2 parts glacial acetic acid, 3.5 parts modified carbon nitride, 0.6 parts aluminum acetylacetonate, 0.8 parts rheology modifier, and 0.5 parts UV auxiliaries; preparation and construction steps are the same as in Example 1.

[0071] Performance: Visible light transmittance 85.3%, near-infrared blocking rate 95.6%, infrared emissivity 0.97, pencil hardness 6H, with optimal cooling effect, suitable for curtain walls with severe western sun exposure.

[0072] Comparative Example 1 (Unmodified pure carbon nitride filler):

[0073] The only difference was that the modified carbon nitride in Example 1 was replaced with ungrafted original C3N4 nanosheets, while the other proportions and processes remained unchanged.

[0074] Test results: The filler was severely aggregated and clumped together; the coating haze was 12.8%, and it appeared visibly white and blurry to the naked eye; sedimentation and stratification occurred after standing for 7 days; scratches appeared after only 8000 abrasion cycles.

[0075] Comparative Example 2 (without metal chelating agent):

[0076] Remove aluminum acetylacetonate from Example 1, otherwise remain unchanged.

[0077] After film formation, the film thickness is uneven, and micron-sized pores exist in some areas; after 300 cycles of high and low temperatures, micro-cracks appear, and the weather resistance life is significantly shortened to less than 5 years.

[0078] Comparative Example 3 (Commercially available ordinary polymer thermal insulation coating):

[0079] Compared with ordinary acrylic-based heat insulation coating of the same thickness, the visible light transmittance is 76.4%, the near-infrared blocking rate is 72.3%, and the pencil hardness is 2H. After 1500 hours of accelerated outdoor aging, the light transmittance decreases by 12.6%, there is no radiation cooling effect, and the indoor temperature drops by only 2.1℃.

[0080] The following is a summary of the overall performance of the coating product from Example 1:

[0081] Excellent interfacial adhesion: The silanol groups in the coating undergo covalent condensation with the silanol groups on the glass surface to form a continuous Si-O-Si anchoring structure, achieving an adhesion grade of 0 in the cross-cut adhesion test; after 1000 cycles of high and low temperature (-30℃~70℃) and 5000 hours of accelerated UV aging, there is no peeling, flaking, or cracking.

[0082] Excellent optical performance: The coating has a visible light (380-780nm) transmittance of 88.7% and a haze of only 1.1%, so indoor lighting is not affected; the near-infrared blocking rate of the entire 780-2500nm band is 94.2%; the infrared emissivity of the 8-13μm atmospheric window is 0.96, and the passive radiation cooling effect is outstanding; compared with the same working conditions in a sealed glass room in summer, the indoor temperature can be reduced by up to 8.6℃, and the air conditioning energy consumption is reduced by more than 37%.

[0083] Outstanding mechanical, abrasion-resistant, and weather-resistant properties: dry film pencil hardness 6H; abrasion-resistant steel wool can be repeatedly scrubbed 25,000 times without scratches, and light transmittance decay is less than 1.2%; inorganic silicon network works synergistically with UV stabilizers, outdoor natural stability service life can reach 15 years; resistant to rain erosion and salt spray for 1200 hours without corrosion or loss of gloss.

[0084] Highly adaptable to construction: The coating exhibits typical shear-thinning properties, and when placed vertically for 72 hours on high-rise curtain walls and sloping skylights, there is no sagging or shrinkage cavities; it cures at room temperature without the need for heating or baking, and a single person can cover an area of ​​up to 210m² per day. 2 .

[0085] Low renovation cost: The raw material cost of paint per square meter is only 45 to 70 yuan. There is no need to remove the original glass. Compared with replacing Low-E glass and high-end heat insulation film, the overall renovation cost is reduced by more than 60%, making it suitable for energy-saving renovation of large-area existing buildings.

[0086] Excellent filler dispersibility: The aminosilane-grafted modified carbon nitride nanosheets are completely monolayer dispersed without agglomeration or precipitation. The coating shows no stratification, whitening, or precipitation after 90 days of static storage, demonstrating excellent storage stability.

[0087] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A high-transmittance, high-wear-resistant glass radiative cooling and heat insulation coating, characterized in that, By weight, the raw materials include: 35-50 parts of tetraethyl orthosilicate; 40-60 parts of anhydrous ethanol; 8-15 parts deionized water; 0.3–1.2 parts of weak acid catalyst; 1.2–3.5 parts of aminosilane coupling agent were used to modify defective g-C3N4 nanosheets; Metal chelating agent 0.15–0.6 parts; 0.2–0.8 parts of shear-thinning rheology modifier; 0.1 to 0.5 parts of UV stabilizer.

2. The high-transmittance, high-wear-resistant glass radiation cooling and heat insulation coating according to claim 1, characterized in that, The aminosilane coupling agent is 3-aminopropyltriethoxysilane; The weak acid catalyst is glacial acetic acid; The metal chelating agent is aluminum acetylacetone; The shear-thinning rheology modifier is a polyether-based rheology modifier; The UV stabilizer is a hindered amine UV stabilizer.

3. The high-transmittance, high-wear-resistant glass radiation cooling and heat insulation coating according to claim 1, characterized in that, The defective g-C3N4 nanosheets were prepared by thermal etching of flake-shaped C3N4 powder at 520°C under a nitrogen atmosphere.

4. The high-transmittance, high-wear-resistant glass radiation cooling and heat insulation coating according to claim 1, characterized in that, The coating has a visible light transmittance of ≥85% in the 380-780nm band, a near-infrared blocking rate of ≥90% in the 780-2500nm band, and an atmospheric window infrared emissivity of ≥0.95 in the 8-13μm band.

5. The high-transmittance, high-wear-resistant glass radiation cooling and heat insulation coating according to claim 1, characterized in that, The dry film of the coating has a pencil hardness of ≥5H and is scratch-free after being rubbed with steel wool 25,000 times.

6. A method for preparing a high-transmittance, high-wear-resistant glass radiation cooling and heat-insulating coating as described in any one of claims 1-5, characterized in that, Includes the following steps: Step 1: The flake-like C3N4 powder is thermally etched to create defects, resulting in defect-modified carbon nitride nanosheets; the defect-modified carbon nitride nanosheets are mixed with anhydrous ethanol and an aminosilane coupling agent, and ultrasonically exfoliated and surface modified to obtain an aminosilane coupling agent modified defect g-C3N4 nanosheet dispersion. Step 2: Mix tetraethyl orthosilicate and anhydrous ethanol evenly, and slowly add a mixture of deionized water and a weak acid catalyst to carry out a hydrolysis and polycondensation reaction to generate silica sol; add a metal chelating agent to the silica sol and stir evenly to obtain a stable silica sol base liquid; Step 3: Add the aminosilane coupling agent modified defect g-C3N4 nanosheet dispersion to the stabilized silica sol substrate solution. After uniform dispersion, add the shear-thinning rheology modifier and the UV stabilizer, and mix evenly to obtain the final product.

7. The preparation method according to claim 6, characterized in that, In step 1, the temperature of the thermal etching process is 520°C, the time is 2 hours, and the atmosphere is nitrogen. The ultrasonic ablation process took 4 hours.

8. The preparation method according to claim 6, characterized in that, In step 2, the hydrolysis-condensation reaction is carried out at room temperature and the stirring time is 2.5 hours.

9. The preparation method according to claim 6, characterized in that, In step 3, the aminosilane coupling agent is added to modify the defective g-C3N4 nanosheets using a high-speed dispersion method. The dispersion speed is 1200 r / min and the time is 40 minutes.